Regulation of Hemichannels and Gap Junction Channels by Cytokines in Antigen-Presenting Cells - Sáez, Pablo J.; Shoji, Kenji F.; Aguirre, Adam; Sáez, Juan C. (Mediators of Inflammation, 2014)
Autocrine and paracrine signals coordinate responses of several cell types of the immune system that provide efficient protection against different challenges. Antigen-presenting cells (APCs) coordinate activation of this system via homocellular and heterocellular interactions. Cytokines constitute chemical intercellular signals among immune cells and might promote pro- or anti-inflammatory effects. During the last two decades, two membrane pathways for intercellular communication have been demonstrated in cells of the immune system. They are called hemichannels (HCs) and gap junction channels (GJCs) and provide new insights into the mechanisms of the orchestrated response of immune cells. GJCs and HCs are permeable to ions and small molecules, including signaling molecules. The direct intercellular transfer between contacting cells can be mediated by GJCs, whereas the release to or uptake from the extracellular milieu can be mediated by HCs. GJCs and HCs can be constituted by two protein families: connexins (Cxs) or pannexins (Panxs), which are present in almost all APCs, being Cx43 and Panx1 the most ubiquitous members of each protein family. In this review, we focus on the effects of different cytokines on the intercellular communication mediated by HCs and GJCs in APCs and their impact on purinergic signaling.